2018
DOI: 10.1007/s00253-018-8776-0
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to prevent the occurrence of resistance against antibiotics by using advanced materials

Abstract: Drug resistance occurrence is a global healthcare concern responsible for the increased morbidity and mortality in hospitals, time of hospitalisation and huge financial loss. The failure of the most antibiotics to kill "superbugs" poses the urgent need to develop innovative strategies aimed at not only controlling bacterial infection but also the spread of resistance. The prevention of pathogen host invasion by inhibiting bacterial virulence and biofilm formation, and the utilisation of bactericidal agents wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 162 publications
0
66
0
Order By: Relevance
“…Currently, multiple health organizations including the U. S. Centers for Disease Control and Prevention [1], the World Health Organization [2] as well as others [3] have identified proliferation of antimicrobial resistance as a global crisis. Antibiotics are globally used in the treatment of bacterial infections [4][5][6] and typically kill most antibioticsusceptible bacterial populations in a relatively short time. However, a small fraction of bacteria can survive and represent a major concern for emergent antibiotic resistance and recurrent infection [7].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, multiple health organizations including the U. S. Centers for Disease Control and Prevention [1], the World Health Organization [2] as well as others [3] have identified proliferation of antimicrobial resistance as a global crisis. Antibiotics are globally used in the treatment of bacterial infections [4][5][6] and typically kill most antibioticsusceptible bacterial populations in a relatively short time. However, a small fraction of bacteria can survive and represent a major concern for emergent antibiotic resistance and recurrent infection [7].…”
Section: Introductionmentioning
confidence: 99%
“…When enough bacteria are reached, the AIs will enable single bacterium to sense other bacteria in their surroundings and could form biofilms. 46 The formed biofilms exhibit higher virulence and resistance compared to planktonic S. aureus. Oyama et al reported that the thick biofilms of S. aureus showed higher virulence to mice livers than the thin biofilms.…”
Section: S Aureus Biofilmsmentioning
confidence: 99%
“…Covering liposomes by synthesized cationichydrophobic chitosan make them go through cell membrane simply and release curcumin in a controlled manner [38,39]. Although liposomes have great biocompatibility, they suffer from some disadvantages such as curcumin leakage and instability while storage, that causes limitation to use them for drug delivery purposes [40,41].…”
Section: Liposomesmentioning
confidence: 99%